Visual behavior and motor responses of novice and experienced wheelchair tennis players relative to the service return - Reina, R.; Moreno, F.; Sanz, D. (Adapted Physical Activity Quarterly, 2007)
The purpose of this study was to determine visual behavior and motor responses between experienced and novice wheelchair tennis players relative to the return in tennis. Novice (n = 7) and Experienced (n = 5) wheelchair tennis players took part in the study. Two series of serves performed to the forehand and the backhand sides were examined in both groups. One series was performed in a video-based setting (two dimensional) and the other one on court (three dimensional). Experienced participants focused initially on the head/shoulders and the free-arm, while novice players focused on the expected ball toss area or followed the ball from the toss to the apex. Results suggest that the experienced players obtain useful information from racket-arm cues during the stroke phase. They also performed faster motor responses as well.